Ser253Leu substitution in PmrB contributes to colistin resistance in clinical Acinetobacter nosocomialis. Issue 1 (1st January 2021) - Yang, Ya-Sung; Jeng, Wen-Yih; Lee, Yi-Tzu; Hsu, Chi-Ju; Chou, Yu-Ching; Kuo, Shu-Chen; Chen, Cheng-Cheung; Hsu, Wei-Jane; the ACTION study group,; Chen, Hsing-Yu; Sun, Jun-Ren
ABSTRACT: Infections caused by extensively drug-resistant (XDR) Acinetobacter nosocomialis have become a challenging problem. The frequent use of colistin as the last resort drug for XDR bacteria has led to the emergence of colistin-resistant A. nosocomialis (ColRAN) in hospitals. The mechanism of colistin resistance in A. nosocomialis remains unclear. This study aimed to investigate the mechanisms underlying colistin resistance in clinical ColRAN isolates. We collected 36 A. nosocomialis isolates from clinical blood cultures, including 24 ColRAN and 12 colistin-susceptible A. nosocomialis (ColSAN). The 24 ColRAN isolates clustered with ST1272 (13), ST433 (eight), ST1275 (two), and ST410 (one) by multilocus sequence typing. There was a positive relationship between pmrCAB operon expression and colistin resistance. Further analysis showed that colistin resistance was related to an amino acid substitution, Ser253Leu in PmrB. By introducing a series of recombinant PmrB constructs into a PmrB knockout strain and protein structural model analyses, we demonstrated that the association between Ser253Leu and Leu244 in PmrB was coupled with colistin resistance in ColRAN. To the best of our knowledge, this is the first study demonstrating that the key amino acid Ser253Leu in PmrB is associated with overexpression of the pmrCAB operon and hence colistin resistance. This study provides insight into the mechanism of colistin resistance in A. nosocomialis .